Beyond the Prototype: Understanding the Challenge of Scaling Hardware Device Production - Khurana, Rushil; Hodges, Steve (CHI 2020, 2020)
The hardware research and development communities have invested heavily in tools and materials that facilitate the design and prototyping of electronic devices. Numerous easy-to-access and easy-to-use tools have streamlined the prototyping of interactive and embedded devices for experts and led to a remarkable growth in non-expert builders. However, there has been little exploration of challenges associated with moving beyond a prototype and creating hundreds or thousands of exact replicas – a process that is still challenging for many. We interviewed 25 individuals with experience taking prototype hardware devices into low volume production. We systematically investigated the common issues faced and mitigation strategies adopted. We present our findings in four main categories: (1) gaps in technical knowledge; (2) gaps in non-technical knowledge; (3) minimum viable rigor in manufacturing preparation; and (4) building relationships and a professional network. Our study unearthed several opportunities for new tools and processes to support the transition beyond a working prototype to cost effective low-volume manufacturing. These would complement the aforementioned tools and materials that support design and prototyping.